Spin Glasses - Bolthausen, Erwin; Bovier, Anton; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Spin glass theory is going through a stunning period of progress while finding exciting new applications in areas beyond theoretical physics, in particular in combinatorics and computer science. This collection of state-of-the-art review papers written by leading experts in the field covers the topic from a wide variety of angles. The topics covered are mean field spin glasses, including a pedagogical account of Talagrand's proof of the Parisi solution, short range spin glasses, emphasizing the open problem of the relevance of the mean-field theory for lattice models, and the dynamics of spin glasses, in particular the problem of ageing in mean field models. The book will serve as a concise introduction to the state of the art of spin glass theory, usefull to both graduate students and young researchers, as well as to anyone curious to know what is going on in this exciting area of mathematical physics.
Random Media and Spin Glasses: An Introduction into Some Mathematical Results and Problems -- Spin Glasses: A Perspective -- Mean Field Models for Spin Glasses: Some Obnoxious Problems -- Much Ado about Derrida's GREM -- Dynamics for Spherical Models of Spin-Glass and Aging -- Local vs. Global Variables for Spin Glasses -- Short-Range Spin Glasses: Results and Speculations.
Keywords: Physics; Probabilities; Statistical physics; Dynamical systems; Physics; Statistical Physics, Dynamical Systems and Complexity; Probability Theory and Stochastic Processes; Electronic books